'All u need is space': Popularizing EU space policy. (August 2017) - Oikonomou, Iraklis
Abstract: The development of EU space policy and its two main programmes, Galileo and Copernicus, has necessitated a parallel process of legitimization of this policy. Popularization, defined as the simplification of a policy in order to be made accessible to the masses and accepted by them, has been a core legitimising tool in the hands of the European Commission, with regular help from experts/industrialists, or 'organic intellectuals'. After establishing popularization conceptually, the analysis illustrates instances of both expert-based and non-expert-based popularization at the Brussels level. It concludes that the process of popularization conceals the most controversial aspects of both Galileo and Copernicus while also producing a 'general interest' that glues together a disparate set of social forces, in favour of EU space programmes and their manufacturers - the European space industry.